Commercial rabbit farming and poverty in urban and peri-urban Kenya - Mutsami, C.; Karl, Stephen (Frontiers Media, 2020)
Research has shown that agricultural commercialization is an effective way of boosting farmers' welfare. Is this true for urban or peri-urban farmers? We attempt to answer this question by assessing the effects of rabbit commercialization on multidimensional poverty among urban farmers in Kenya. While previous studies have analyzed commercialization in terms of crops, small livestock such as rabbit has received little attention. Additionally, most studies use income to capture poverty without considering other deprivations such as education, health and living standards. Here, we assess the effect or rabbit commercialization on multidimensional poverty among urban and peri-urban farmers. Data from 260 respondents is used. Findings show that rabbit commercialization is associated with a decrease in multidimensional poverty among urban and peri-urban farmers. This means that livestock commercialization has a potential of improving living standards of urban poor. Policy implication of this finding is that there is need to focus on promotion of commercialization among smallholder farmers through provision of necessary infrastructure such as roads and refrigerators and institutions such credit, inputs and output markets.